2018
DOI: 10.1080/19420862.2018.1490119
|View full text |Cite
|
Sign up to set email alerts
|

Extending human IgG half-life using structure-guided design

Abstract: Engineering of antibodies for improved pharmacokinetics through enhanced binding to the neonatal Fc receptor (FcRn) has been demonstrated in transgenic mice, non-human primates and humans. Traditionally, such approaches have largely relied on random mutagenesis and display formats, which fail to address related critical attributes of the antibody, such as effector functions or biophysical stability. We have developed a structure- and network-based framework to interrogate the engagement of IgG with multiple Fc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 54 publications
(63 reference statements)
4
61
0
Order By: Relevance
“…To further assess the putative Fab and FcRn interactions, we analyzed the IgG-FcRn complex structure by negative stain electron microscopy, and observed several distinct classifications of IgG-FcRn complex ( Figure 2 ). The Fab arms of IgG appear to be highly dynamic as previously observed, 31 with multiple conformations previously predicted by Booth et al 32 These include the canonical Y-shaped conformation ( Figure 2(a and d )), a T-shaped conformation ( Figure 2(b and e )) or a mixed Y/T conformation ( Figure 2(c and f )). In addition, we observed that the soluble form of FcRn can bind to the IgG at either 1:1 ( Figure 2(b -d)) or 2:1 ( Figure 2(e -f)) stoichiometry.…”
Section: Resultssupporting
confidence: 76%
“…To further assess the putative Fab and FcRn interactions, we analyzed the IgG-FcRn complex structure by negative stain electron microscopy, and observed several distinct classifications of IgG-FcRn complex ( Figure 2 ). The Fab arms of IgG appear to be highly dynamic as previously observed, 31 with multiple conformations previously predicted by Booth et al 32 These include the canonical Y-shaped conformation ( Figure 2(a and d )), a T-shaped conformation ( Figure 2(b and e )) or a mixed Y/T conformation ( Figure 2(c and f )). In addition, we observed that the soluble form of FcRn can bind to the IgG at either 1:1 ( Figure 2(b -d)) or 2:1 ( Figure 2(e -f)) stoichiometry.…”
Section: Resultssupporting
confidence: 76%
“…Structurally, the Del mutation is well tolerated, as demonstrated by the conserved thermal stability. In this aspect, the Del mutation is an improvement over the well-known FcRn + YTE variant, which increases mAb serum t 1/2 in humans at the cost of highly decreasing the thermal stability of the mAb (83). In addition, as assessed by two in silico algorithms that predict epitope binding to human HLA alleles (Antitope [iTope and TCED] and Lonza [Epibase]), the Del mutation failed to generate neo-epitopes with consensus HLA-binding residues.…”
Section: Discussionmentioning
confidence: 99%
“…Monoclonal antibodies (mAbs) to CSP have been proposed as new infection-blocking interventions [9][10][11][12], and protection by mAbs can be expected to wane with the half-life of the antibody in serum. While altering the sequence of mAb Fc regions has been used to extend serum half-life of mAbs [13], an important additional approach for improving the durability of protection is to identify mAbs effective at lower concentrations. Identification and development of such potent antibodies will require assays that reliably measure their functional activity.…”
Section: Introductionmentioning
confidence: 99%